Uncinate fasciculus microstructural organisation and emotion recognition in schizophrenia: controlling for hit rate bias - Stevens, Matthew; Ní Mhurchú, Síle; Corley, Emma; Egan, Ciara; Hallahan, Brian; McDonald, Colm; Donohoe, Gary; Burke, Tom (Frontiers in Behavioral Neuroscience, 2024)
Introduction Schizophrenia (SCZ) is a complex neurodevelopmental disorder characterised by functional and structural brain dysconnectivity and disturbances in perception, cognition, emotion, and social functioning. In the present study, we investigated whether the microstructural organisation of the uncinate fasciculus (UF) was associated with emotion recognition (ER) performance. Additionally, we investigated the usefulness of an unbiased hit rate (UHR) score to control for response biases (i.e., participant guessing) during an emotion recognition task (ERT). Methods Fifty-eight individuals diagnosed with SCZ were included. The CANTAB ERT was used to measure social cognition. Specific ROI manual tract segmentation was completed using ExploreDTI and followed the protocol previously outlined by Coad et al. (2020). Results We found that the microstructural organisation of the UF was significantly correlated with physical neglect and ER outcomes. Furthermore, we found that the UHR score was more sensitive to ERT subscale emotion items than the standard HR score. Finally, given the association between childhood trauma (in particular childhood neglect) and social cognition in SCZ, a mediation analysis found evidence that microstructural alterations of the UF mediated an association between childhood trauma and social cognitive performance. Discussion The mediating role of microstructural alterations in the UF on the association between childhood trauma and social cognitive performance suggests that early life adversity impacts both brain development and social cognitive outcomes for people with SCZ. Limitations of the present study include the restricted ability of the tensor model to correctly assess multi-directionality at regions where fibre populations intersect.